KKN KEBENCANAAN: DESA TANGGUH BENCANA SEBAGAI UPAYA PEMULIHAN EKONOMI DAN KONDISI SOSIAL PASCA BANJIR BANDANG - Rahmad Solling Hamid; Salju Salju; Suharnita Suharnita; Pelandira Pelandira; Nur Fadillah; Naina Lusi; Dwi Rahmatya Ruddin (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The flash flood disaster in Maipi, Masamba, North Luwu Regency occurred on July 13, 2020, has caused various problems. The community's unpreparedness in dealing with flash floods disasters creates psychological stress (traumatic) as well as social and economic impacts. This community service aimed to assist the community in increasing their knowledge, abilities, and independence in facing and overcoming disaster problems after flash floods. The method used is by conducting disaster mitigation training and agricultural extension agents. The benchmarks for the success of this activity are, first, increasing knowledge about disasters and ways of dealing with them in community groups. Second, the increased capacity of community groups regarding the optimization of land damaged by flash floods as a forum for the community to produce vegetables with economic value.